Queensland Genomics: an adaptive approach for integrating genomics into a public healthcare system - Miranda E. Vidgen (Nature Portfolio, 2021)
Abstract The establishment of genomics in health care systems has been occurring for the past decade. It is recognised that implementing genomics within a health service is challenging without a system-wide approach. Globally, as clinical genomics implementation programs have matured there is a growing body of information around program design and outcomes. Program structures vary depending on local ecosystems including the health system, politics and funding availability, however, lessons from other programs are important to the design of programs in different jurisdictions. Here we describe an adaptive approach to the implementation of genomics into a publicly funded health care system servicing a population of 5.1 million people. The adaptive approach enabled flexibility to facilitate substantial changes during the program in response to learnings and external factors. We report the benefits and challenges experienced by the program, particularly in relation to the engagement of people and services, and the design of both individual projects and the program as a whole.